The Institution of Riba: Qur’anic Prohibition, Scholarly Interpretations, and the Dichotomy between Usury and Interest - Ganaie, Bilal Ahmad; Riyaz Ahmad Bhat (Penerbit Hellow Pustaka, 2025)
Riba is a topic of considerable debate in contemporary scholarship. Its prohibition is central to Islamic economic and moral philosophy, serving as a foundational principle that distinguishes Islamic finance from conventional financial systems. The Qur’an characterizes riba as a source of injustice and exploitation that undermines social equity and compassion. The Sunnah reinforces its gravity by categorizing it among the most serious transgressions. This study investigates Islamic teachings regarding the prohibition of riba. Although the prohibition is explicit, some scholars have challenged the operational definition of riba and presented arguments in its favor. This research critically evaluates these arguments, examines contextual interpretations of riba within changing economic frameworks, and traces the historical evolution of the distinction between usury and interest to determine its consistency with Islamic jurisprudence. The results demonstrate that the prohibition of riba reflects Islam’s commitment to promoting justice, equity, and moral integrity in economic interactions.